1992
DOI: 10.1007/bf00296775
|View full text |Cite
|
Sign up to set email alerts
|

The role of magnesium on the structure of biological apatites

Abstract: X-ray diffraction, infrared absorption spectroscopy, and chemical investigation have been carried out on deproteinated samples of turkey leg tendon at different degrees of calcification. The inorganic phase consists of poorly crystalline B carbonated apatite. On increasing calcification, the apatite crystal size, as well as its thermal stability, increase while the relative magnesium content is reduced. On the other hand, synchrotron X-ray diffraction data clearly indicate that apatite lattice parameters do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
148
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(167 citation statements)
references
References 23 publications
9
148
0
Order By: Relevance
“…However, this work is consistent with other studies in which no such transformation was observable [55,15]. This difference has been ascribed to greater Ca/P ratios and lower amounts of HPO 4 À and Mg [56]. It has been assumed that the formation of different mineral phases could be a function of individual age [15,57].…”
Section: Overall High Temperature Modification Process and Indicatorssupporting
confidence: 92%
“…However, this work is consistent with other studies in which no such transformation was observable [55,15]. This difference has been ascribed to greater Ca/P ratios and lower amounts of HPO 4 À and Mg [56]. It has been assumed that the formation of different mineral phases could be a function of individual age [15,57].…”
Section: Overall High Temperature Modification Process and Indicatorssupporting
confidence: 92%
“…Furthermore, magnesium promotes the thermal conversion of HA into 13-TCP, where it can partially replace calcium (Bigi et al, 1988;Bigi et al, 1992;Bigi et al, 1993). The modifications of the values of the HA lattice constants induced by ionic substitution are generally in agreement with the difference in ionic radii between calcium and substituent ions (Heijligers, Driessens & Verbeck, 1979;Bigi, Gazzano, Ripamonti, Foresti & Roveri 1986;Bigi et al, 1989;Bigi et al, 1991).…”
Section: Introductionmentioning
confidence: 56%
“…In addition, previous reports have shown that bone quality deteriorates under a low Mg condition [14,15], and that subjects at low serum Mg levels are at risk for bone fractures [12]. It has been reported that dietary Mg supplementation affected bone metabolism and dynamic strength of bone in ovariectomized rats [16].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Mg deficiency could inhibit the synthesis of 1,25-dihydroxy vitamin D (1,25(OH) 2 D) [9][10][11] as well as its action on bone [11]. Accumulating data have shown that a long-term Mg deficiency and resulting hypomagnesemia could cause osteoporosis and bone fractures through these dysfunctions of PTH and vitamin D action [12,[13][14][15][16][17][18][19]. However, other studies have shown no relationship between Mg deficiency and osteoporosis [20][21][22], and it still seems to be controversial whether or not Mg deficiency could cause osteoporosis.…”
mentioning
confidence: 99%